2015
DOI: 10.11648/j.cb.20150304.11
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Thermal, and Spectroscopic Characterization of Biofield Energy Treated Murashige and Skoog Plant Cell Culture Media

Abstract: Abstract:The Murashige and Skoog medium (MS media) is a chemically defined and widely used as a growth medium for plant tissue culture techniques. The present study was attempted to evaluate the impact of biofield energy treatment on the physical, thermal, and spectral properties of MS media. The study was performed in two groups; one was kept as control while another was subjected to Mr. Trivedi's biofield energy treatment and coded as treated group. Afterward, both the control and treated samples were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…the isotopic abundance ratio of P M+1 /P M ( 13 C/ 12 C or 2 H/ 1 H or 15 N/ 14 N) in 4-bromoaniline was increased after biofield energy treatment up to 368.3% [18]. The isotopic abundance ratio of P M+2 /P M ( 18 O/ 16 O or 37 Cl/ 35 Cl) in biofield treated 2,4-dichlorophenol was increased by 40.57%, respectively [20]. Biofield energy is an electromagnetic field existed in an around the human body [21][22][23].…”
Section: Ortho-and Meta-nitrophenol (O-and M-nitrophenol)mentioning
confidence: 98%
“…the isotopic abundance ratio of P M+1 /P M ( 13 C/ 12 C or 2 H/ 1 H or 15 N/ 14 N) in 4-bromoaniline was increased after biofield energy treatment up to 368.3% [18]. The isotopic abundance ratio of P M+2 /P M ( 18 O/ 16 O or 37 Cl/ 35 Cl) in biofield treated 2,4-dichlorophenol was increased by 40.57%, respectively [20]. Biofield energy is an electromagnetic field existed in an around the human body [21][22][23].…”
Section: Ortho-and Meta-nitrophenol (O-and M-nitrophenol)mentioning
confidence: 98%
“…Biofield Energy Healing Treatment (The Trivedi Effect ® ) has been published in numerous peerreviewed science journals due to its significant impacts in the science fields of biotechnology, genetics, cancer, microbiology, materials science, agriculture, and pharmaceuticals. These publications reported that Biofield Energy Treatment (The Trivedi Effect ® ) has the astounding capability to transform the physical, structural, chemical, thermal and behavioral properties of several pharmaceuticals [23][24][25], nutraceuticals [26,27], organic compounds [28][29][30], metals and ceramics in materials science [31][32][33], improve the overall productivity of crops [34][35][36], as well as modulate the efficacy of various living cells [37][38][39][40]. Although magnesium gluconate exhibits the highest bioavailability and moderate solubility in water in comparison to other magnesium salts, humans still face problems in achieving their daily requirements of magnesium [41].…”
Section: Introductionmentioning
confidence: 99%
“…The Biofield Energy Healing Treatment (The Trivedi Effect ® ) has been published in numerous peerreviewed science journals due to its significant impacts in the science fields of biotechnology, genetics, cancer, microbiology, materials science, agriculture, and pharmaceuticals. These publications reported that the Biofield Energy Treatment (The Trivedi Effect ® ) has the astounding capability to transform the physical, structural, chemical, thermal and behavioral properties of several pharmaceuticals [23][24][25], nutraceuticals [26,27], organic compounds [28][29][30], metals and ceramic in materials science [31][32][33], and improve the overall productivity of crops [34][35][36] as well as to modulate the efficacy of the various living cells [37][38][39][40]. Although magnesium gluconate exhibits the highest bioavailability and moderate solubility in water in comparison to other magnesium salts, humans still face problems in achieving their daily requirements of magnesium [41].…”
Section: Introductionmentioning
confidence: 99%